Willingness to pay (WTP) for heat-tolerant maize hybrids in the Mid-Western Terai region of Nepal - Kulkarni, Atul Prabhakar; Tripathi, Mahendra Prasad; Gautam, Damodar; Koirala, Keshab Babu; Kandel, Manoj; Regmi, Dhruba; Sapkota, Sudha; Zaidi, Pervez H. (MDPI, 2023)
High atmospheric temperatures can reduce maize production in different parts of Asia. Heat stress is the major driving force behind the need for varietal development that confers a heat tolerance trait (drought + heat tolerant) to maize hybrids. CIMMYT has developed heat-tolerant maize hybrids and deployed them in the market in collaboration with NARS partners. This study was conducted to estimate farmers’ willingness to pay for heat-tolerant maize hybrids in the Terai region of Nepal. A socioeconomic survey of 404 randomly selected maize-growing households was conducted to estimate farmers’ willingness to pay using the contingent valuation method. Given the economic importance of heat-tolerant maize hybrids in maize cultivation, the survey showed that the average WTP for heat-tolerant maize hybrids was 71% more than that for the current varieties in the market, including overall seed sources and subsidized seed. Without a subsidy, the farmers’ WTP price was at a 19% premium compared to the average price paid for conventional hybrids. Factors such as education, owning land, the interaction of hybrid adopters and owning land, soil depth, the number of goats/sheep, and the semi-pucca homes of households influenced the WTP for heat-tolerant maize hybrids. Heterogeneous demand was observed with respect to years of hybrid maize cultivation, farmers’ association with the network group, and the gender of the head of the household. In the context of climate change and global warming scenarios, Nepal’s agriculture policy should prioritize increasing domestic seed production and the distribution of heat-tolerant maize hybrids through a public–private partnership model.